Invaders Tops Preliminaries - Blood, Peter (Daily Express)
Trintoc Invaders was able to convince 20,000 pan lovers and five judges that Steve Achaiba's scintillating arrangement of Merchant's 'Pan in Danger' was the best performed piece at the North/East Panorama preliminaries. However, the standard of pan was mediocre and most patrons seemed more contented dancing to the sounds of house disc jockey than listening to pan.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Popular music -- Trinidad and Tobago; Panorama (Musical festival); Steel band music -- Trinidad and Tobago